2021
DOI: 10.3390/medicina57070645
|View full text |Cite
|
Sign up to set email alerts
|

In-Season Internal and External Workload Variations between Starters and Non-Starters—A Case Study of a Top Elite European Soccer Team

Abstract: Background and Objectives: Interpretation of the load variations across a period seems important to control the weekly progression or variation of the load, or to identify in-micro- and mesocycle variations. Thus, the aims of this study were twofold: (a) to describe the in-season variations of training monotony, training strain and acute:chronic workload ratio (ACWR) through session ratings of perceived exertion (s-RPE), total distance and high-speed running (HSR); and (b) to compare those variations between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 37 publications
5
29
1
Order By: Relevance
“…Therefore, and despite there being players who are the preferred starters, regular changes in the main squad may occur as a function of such intensified periods, which helps to justify the lack of differences according to statuses. While the absence of differences in the analysis of starters versus reserve players is in agreement with the current evidence [ 24 , 50 ], the playing position had a significant influence in an almost matched male sample considering Hooper’s Index measures [ 30 ]. In this sense, it is necessary to point out the possibility that, in women’s soccer, the traditional position-related outputs might be more limited or even non-existent.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore, and despite there being players who are the preferred starters, regular changes in the main squad may occur as a function of such intensified periods, which helps to justify the lack of differences according to statuses. While the absence of differences in the analysis of starters versus reserve players is in agreement with the current evidence [ 24 , 50 ], the playing position had a significant influence in an almost matched male sample considering Hooper’s Index measures [ 30 ]. In this sense, it is necessary to point out the possibility that, in women’s soccer, the traditional position-related outputs might be more limited or even non-existent.…”
Section: Discussionsupporting
confidence: 88%
“…Of note, when the training duration was shortened (e.g., weeks 2 and 7), TM and TS were also impacted in the same direction of declines, thus suggesting that it could be a reasonable strategy when it is necessary to adequately recover players. Notwithstanding, TM and TS peaked respectively in weeks 1 and 2, which is similar to research into male soccer [ 24 , 36 ] and might illustrate the challenge of female athletes to deal with training demands imposed at the beginning of a season.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This study is a descriptive-longitudinal approach and followed a cohort design conducted during a 12-months period from June 2017 to July 2018 (4 weeks during the preseason and 46 weeks during the in-season). An approach used in previous studies was adapted in which each month corresponded to a mesocycle [26][27][28].…”
Section: Designmentioning
confidence: 99%
“…Nevertheless, there is scarce information regarding the intragroup differences in starting and non-starting soccer players with respect to the weekly TM and TS at different speed zones and across the periods of a full season. Recently, and in opposition to the previous information, the study from Oliveira et al [16] found that both starters and nonstarters presented small differences. The same authors suggested that training workload adjustments applied over the season helped to reduce differences between player status.…”
Section: Introductionmentioning
confidence: 74%